To solve the system using substitution, we substitute one equation into the other equation and solve for the variable.
Given equations:
1) y = 8 - x
2) y = 2 - y
Substitute equation 2) into equation 1):
2 - y = 8 - x
Rearrange the equation:
y = 8 - x - 2
Combine like terms:
y = 6 - x
Now that we have an expression for y, we can substitute it back into equation 2):
6 - x = 2 - (6 - x)
Simplify the equation:
6 - x = 2 - 6 + x
Move variables to one side and constants to the other side:
6 + 6 = 2 + x + x
12 = 2x + 2
Move the constants to one side:
12 - 2 = 2x
10 = 2x
Divide by 2 to solve for x:
x = 5
Substitute the value of x into equation 1) to solve for y:
y = 8 - x
y = 8 - 5
y = 3
The solution to the system is the ordered pair (x, y) = (5, 3).
Therefore, the correct response is: Image with alt text: the ordered pair (5, 3)
Solve the system using substitution. y=8-x y=2-y(1 point) Responses Image with alt text: the ordered pair (5, 13) Image with alt text: the ordered pair (13, negative 5) Image with alt text: the ordered pair (3, 5)
1 answer